A Qualitative Landscape of Trauma: Mental Health Professionals’ Therapeutic Work Processes with Adult Clients who Have Experienced Trauma - Šaltenytė, Ieva; Kaluževičiūtė, Greta (Psichologija, 2024)
Most people experience potentially traumatic events at least once throughout their lifetimes. Even if this event does not lead toward posttraumatic stress disorders, mental health can be affected significantly. The difficulties caused by traumatic experiences are often addressed in psychotherapy, therefore understanding the specifics of trauma work and the challenges faced both by clients with traumatic experiences and by therapists providing support is important. This study explores and describes the views and experiences of psychotherapy practitioners working in the field of trauma with adult clients. Thirty mental health professionals participated in the study. Thematic analysis of open-ended survey responses revealed three main themes: 1) the vulnerability of the therapeutic process, 2) experiencing trauma work, and ٣) helping yourself to help others. Trauma work is described as a slow process that calls for patience, high-level care, and attentiveness in addressing clients’ pain. Clients often mistrust others and therapists put a great effort into establishing trusted relationships with them. Therapists experience a high emotional load, often feel hopeless, but also find their work rewarding and meaningful when clients make progress. Most therapists emphasize the importance of helping yourself: studying and preparing for trauma work, understanding personal traumatic experiences, and taking excellent care of one’s psychological well-being. The study revealed the subjective complexity of therapeutic trauma work. The insights can be valuable for the development and/or review of therapy training programs, supervisors, and therapists looking for information about their professional challenges in working with trauma.
Keywords: psychological trauma; psychotherapy; mental health professionals; qualitative survey